TELISIK KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA : BERPENGARUHKAH TERHADAP KINERJA KARYAWAN - Aprih Santoso; Sari Wulandari (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of compensation, motivation, and work environment on the performance of employees of PT. Cahaya Agung Cemerlang (CAC) Godong Kab. Grobogan this study uses employee performance as the dependent variable and as an independent variable is compensation, motivation work environment. The population in this study were employees of sales at PT. Cahaya Agung Cemerlang (CAC) Godong Kab. Grobogan, the population in this study was 43 people. The sampling technique in this study uses saturated sampling (census) in which all members of the population are sampled. The analytical method used is multiple linear regression analysis. The results of this research show that Compensation, Motivation, and Work Environment affect the performance of employees of (CAC) Godong Kab. Grobogan.